An intelligent traffic management system. - Khatun, Sabira; Chong , Jin Hui; Bakhraiba, Ahmed (2008)
The present invention relates to a smart vehicle identification device with the ability to determine the identity of vehicles on city streets and/or highways. Possible applications are automobile safety, intelligent highway safety systems, accident avoidance, accident elimination, collision avoidance, blind spot detection, anticipatory sensing, automatic vehicle control, intelligent cruise control and automotive navigation. The invention comprises of three stages namely; network, RFID, server and the car control and safety. An FPGA based active RFID tag is mounted on the top of the auto driven car (while only an efficient RFID tag is mounted on top of any other not auto-driven car) with omni-directional antenna. Active efficient RFID readers are placed at the lamp posts along the road, which scans the ID of the car and send to the server. The server has database about the location of each RFID reader. The server then detects the location of the car and calculates the shortest path and sends a wireless route-guidance signal to the cars to save time and fuel consumption. This signal is stored in the micro-controller in the auto-driven car and updated time-to-time. The auto-driven car also equipped with infra-red sensor, sonar sensor, DC motor and stepper motor to provide the safety.